1991
DOI: 10.1128/aac.35.11.2450
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Pseudomonas aeruginosa against ciprofloxacin and beta-lactams by homologous alginate

Abstract: Pseudomonas aeruginosa-derived alginate but no other neutral and negatively charged polysaccharides protected mucoid and nonmucoid strains of that organism against ciprofloxacin, gentamicin, ticarcillin, and ceftazidime. Data indicate that alginate has an intrinsic protective effect which is independent of diffusion, charge, or biofilm phenomena.The role of Pseudomonas aeruginosa in lung infections of patients with cystic fibrosis (CF) is well documented (1, 9, 12), but the means by which mucoid strains surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 14 publications
2
49
0
Order By: Relevance
“…Increased production of alginate decreases the susceptibilities of bacteria growing in biofilms to numerous antibiotics. The penetration of antibiotics through the biofilm may be reduced due to binding to alginate, as has been reported for aminoglycosides, e.g., tobramycin (1,15,21,23). However, exposure to tobramycin does not affect the expression of alginate in P. aeruginosa biofilms (PAO1), as reported by Whiteley et al (50).…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…Increased production of alginate decreases the susceptibilities of bacteria growing in biofilms to numerous antibiotics. The penetration of antibiotics through the biofilm may be reduced due to binding to alginate, as has been reported for aminoglycosides, e.g., tobramycin (1,15,21,23). However, exposure to tobramycin does not affect the expression of alginate in P. aeruginosa biofilms (PAO1), as reported by Whiteley et al (50).…”
mentioning
confidence: 49%
“…Chronic bronchopulmonary infection with P. aeruginosa is the major factor leading to the increased morbidity and premature mortality seen in patients with cystic fibrosis (CF) (26). The establishment of biofilms by alginate-producing P. aeruginosa strains is the most common mode of growth in CF patients with chronic lung infections, with the biofilms providing a protected environment against the host immune system and a number of antibiotics (1,4,15,23). The presence of P. aeruginosa strains with the mucoid phenotype in CF patients with chronic lung infections is a marker of a poor prognosis (20).…”
mentioning
confidence: 99%
“…The negatively charged EPS produced by P. aeruginosa has been shown to bind to positively charged antibiotics such as aminoglycosides, but the resulting reduction in the diffusion coefficient within the biofilm has been shown to be insufficient to explain the observed changes in the susceptibility of the biofilm (29). The mucoid glycocalyx associated with the P. aeruginosa biofilm also protects the stuck cells against neutral antibiotics, indicating that factors other than charge are responsible for the reduced efficacies of antibiotics (22). Costerton (8) observed that ␀-lactam antibiotics can penetrate the entire thickness of the biofilm and so concluded that protection of biofilm cells is not really linked to slime.…”
Section: Discussionmentioning
confidence: 99%
“…aeruginosa possesses several virulence factors which aid in its pathogenicity and resistance to antimicrobial agents (Cane & Walsh, 1999;Lee, et al, 2003). These include: possession of mucus-an alginate capsule (Hodges, & Gordon, 1991;Owlia, et al, 2001;Ahangarzadeh-Rezaee, et al, 2002), presence of exoenzymes S, elastase and phospholipase C (Slack, & Nichols, 1981;Livermore, 1987;Behzadiyan-Nejad, et al, 1989); and an active Chaperone Usher pathway (Ichimiya, et al, 1994;Vallet, et al, 2001). P. aeruginosa has been shown to be resistant to several antibiotics.…”
Section: Introductionmentioning
confidence: 99%